Sistem Rekomendasi Pengadaan Bahan Material Perusahaan Pengembang Properti Menggunakan Metode ARIMA dan AHP - Hasyim Asy'ari; Endang Setyati; Suhatati Tjandra (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2023)
This research aims to help companies to be able to estimate the procurement of materials in property development, control material stocks in warehouses, and determine which suppliers can support to meet these needs with predetermined criteria, namely the supplier's distance to the project location, delivery speed, suitability orders, good quality materials and affordable prices. The method used to estimate the quantity of material procurement in maintaining the availability of material stock in the warehouse is the Auto Regressive Moving Average (ARIMA) method and the Analytical Hierarchy Process (AHP) as a method for determining material suppliers. The results of this study indicate that the average percentage of forecasting errors is 6.1%. As for the selection of material suppliers, the AHP method can recommend which suppliers are eligible to be selected based on predetermined criteria, then the results are sorted based on the highest ranking.